A Facile and Catalyst-Free Microwave-Promoted Multicomponent Reaction for the Synthesis of Functionalised 1,4-Dihydropyridines With Superb Selectivity and Yields - Kerru, Nagaraju (Front Chem, 2021)
We report a highly efficient green protocol for developing a novel library of 1,2,4-triazole-tagged 1,4-dihydropyridine analogs through the one-pot process from the four-component fusion of the 1H-1,2,4-triazol-3-amine with different chosen aldehydes, diethyl acetylenedicarboxylate, and active methylene compounds in a water medium under microwave irradiation and catalyst-free conditions. Excellent yields (94–97%) of the target products were achieved with high selectivity with a short reaction time (<12 min) at room temperature. The structures of the synthesized pyrimidine analogs were established by NMR and HRMS spectroscopic analysis. Simple workup, impressive yields, no column chromatography, green solvent, rapid reaction, and excellent functional group tolerance are the benefits of this protocol.